THE COMPARISON OF LATTICE BOLTZMANN METHOD LTRT-MODEL AND LBGK-MODEL FOR ADVECTION-DIFFUSION EQUATION MODELING - (NIM 20206008), SUGIYANTO
The objective of this thesis is to evaluate the two-dimensional lattice Boltzmann method (LBM) as numerical method to solve mass transport problem especially advection-diffusion equation. This study investigates and compares the stability and accuracy of the LBM with two-relaxation-time collision operator (LTRT) model with the single-relaxation-time or Bhatnagar-Gross-Krook (LBGK) model. The program was verified using two-dimensional transport equation with Gaussian initial condition. The result of computation was compared with analytical solution of the problem. The LBGK model was compared with the LTRT model by varying the linier equlibrium distribution functions (EDFs) and quadratic EDFs and varying the relaxation time in D2Q9 lattice. The program was implemented to solve the two-dimensional transport in a rectangular region problem, and the results LTRT are in good agreement with other numerical solutions methods obtained by Yeh with 3DLEWASTE and Hardyanto with 3DFEMWATER-LHS.